PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS GAME EDUKASI MENGGUNAKAN MODEL INKUIRI TERBIMBING PADA MATERI LISTRIK STATIS DI SMP KRISTEN RURUKAN - Mamuaja, Majesti; Rondonuwu, Anneke T.; Rungkat, Jovialine (SOSCIED, 2024)
Development of Student Worksheets (LKPD) Based on Educational Games Guided Inquiry Model on Static Electricity Material at Rurukan Christian Middle School. The aim of this research is to know how to develop LKPD, knowing feasibility and response to produce a product in the form of a Participant Worksheet Educational Game-Based Education with Guided Inquiry Model on Electricity Material Static at Rurukan Christian Middle School which can increase motivation to learn from learners. The design used in this research is the ADDIE model with stages (1) Analysis, (2) Design, (3) Development, (4) Implementation. Results of development research and data analysis that have been carried out shows an educational game-based LKPD with a guided inquiry model on the material Static electricity according to media expert validators shows a percentage of 93.74% with The interpretation criteria are very feasible and according to the validator, the material expert shows percentage of 86.28% with very feasible interpretation criteria. Level of attractiveness based on teacher responses, it shows a percentage of 92.1% according to the criteria interpretation strongly agrees. The level of attractiveness is based on group test responses small indicates a percentage of 93% with the interpretation criteria of strongly agreeing.The level of interest in students' responses in the large group test shows percentage of 90.8% with interpretation criteria strongly agree. Through this data shows an educational game-based LKPD with a guided inquiry model on the material Static electricity is interesting and can be used as a learning medium learning process for teachers and students